The contribution of academic advising to fostering entrepreneurial intentions in higher education - Anos, Chitamba; Verna, Yearwood; Matthys, Swanepoel; Gabriel, Myeza; Mbona, Sizwe (Edelweiss Applied Science and Technology, 2025)
Academic counseling plays a crucial role in student support within higher education institutions, contributing not only to academic achievement but also to career development and entrepreneurial initiatives. This study investigates the impact of academic advising on fostering entrepreneurial intentions among students at the Durban Institute of Technology (DUT) in South Africa. Utilizing planned behavioral theory as a conceptual framework, this research explores how academic guidance affects students’ attitudes toward entrepreneurship, subjective norms, and perceived behavioral control, ultimately influencing their intention to engage in entrepreneurial activities. Data analysis conducted using SPSS 30.0 revealed a significant positive correlation between academic counseling and entrepreneurial intentions (r = 0.612, p < 0.001). Key findings indicate that academic advising enhances entrepreneurial awareness and provides essential information while also highlighting a gap in connecting students with practical resources, such as business planning and funding support. Additionally, this study reveals that Generation Z students prefer digital advisory tools, although they still value traditional learning methods for guidance. Recommendations include expanding mentoring programs, enhancing collaboration between universities and industries, and leveraging technology to improve advisory services. Moreover, addressing gender-influenced and culturally integrated advisory practices can support underrepresented student groups in entrepreneurship. Future research should focus on the longitudinal effects of academic advising on entrepreneurial success and explore best practices for integrating entrepreneurship into academic counseling models.